Islamic NGOs in Bangladesh development, piety and neoliberal governmentality - Salehin, Mohammad Musfequs (Routledge contemporary South Asia series, 2016)
NGOs (Non-Governmental Organizations) have emerged in both a development and aid capacity in Bangladesh, providing wide-reaching public services to the country's population living in extreme poverty. However, resistance to and limitations of NGO-led development - which in conjunction with Bangladesh's social transformation - led to a new religious-based NGO development practice. Looking at the role of Islamic NGOs in Bangladesh, the book investigates new forms of neoliberal governmentality supported by international donors. It discusses how this form of social regulation produces and reproduces subjectivities, particularly Muslim women subjectivity, and has combined religious and economic rationality, further complicating the boundaries and the relationship between Islam, modernity, and development. The book argues that both secular and Islamic NGOs target women in the name of empowerment but more importantly as the most reliable partners to meet their debt obligations of micro-financing schemes, including shari'a-based financing